A Unified Synthetic Approach to Polyketides Having Both Skeletal and Stereochemical Diversity - Shang, Shiying (2007)
[Image: see text] An efficient systematic approach to the diversity-oriented synthesis of polyketides has been developed to provide both skeletal and stereochemical diversity. Each synthetic intermediate is also a desired polyketide fragment and no protecting group manipulations are required. A first-generation synthesis provides a 74-membered polyketide library comprising six different skeletal classes, each in one to five steps from propargylic alcohol precursors. A study of epoxyol opening reactions revealed unusual reactivity trends based on epoxide configuration.